APPLICATION OF GREEN EXTRACTION METHODS TO RESVERATROL EXTRACTION FROM PEANUT (ARACHIS HYPOGAEA L.) SKIN - SYAHDI, REZI RIADI; NADYANA, RATNA; PUTRI, RIZQI HERU; SANTI, ROSEDIANA; MUN’IM, ABDUL (International Journal of Applied Pharmaceutics, 2020)
Objective: This study compared the maceration extraction method with non-conventional extraction methods such as ultrasound-assisted extraction (UAE) and microwave-assisted extraction (MAE). Methods: To obtain resveratrol, various conditions were optimized: Solvent types (organic solvent [i.e. 70% ethanol] and green solvents [i.e. natural deep eutectic solvent (NADES) and ionic liquid (IL)]) and extraction methods. The resveratrol content in the extracts was analyzed by high-performance liquid chromatography. Results: It was determined that resveratrol extracted by UAE with NADES was composed of choline chloride–oxalic acid when the following conditions were used: The solid/liquid ratio of 1:20 (g/mL) and the extraction time of 15 min. These conditions produced higher resveratrol content (0.049 mg/g dry weight) than that using MAE with 70% ethanol (0.011 mg/g dry weight). However, the maceration method yielded the highest amount of resveratrol (0.221 mg/g dry weight), and MAE with IL produced the smallest amount of resveratrol (0.157 × 10−3 mg/g dry weight). Conclusion: Peanut skin extracted using the maceration method produced the highest amount of resveratrol compared to that using other methods.